Impact of annual financial results announcement on security prices : case of Singapore stock market - See Tho, Soat Ching (2008)
This study examines the existence of abnormal returns based on published financial results for the period from 1993 to 1996. It further tests the correlation between the percentage change in abnormal returns and the percentage change in the earnings, dividends, debt-equity and cash flow in 1993. This study is based on 41 local stocks traded on the Stock Exchange of Singapore (SES) between 1993 and 1996.